Evidence-Based Treatment of Diabetic Macular Edema. (2nd January 2017) - Barham, Rasha; El Rami, Hala; Sun, Jennifer K.; Silva, Paolo S.
ABSTRACT: Diabetes mellitus is a chronic disease that affects 415 million people worldwide. Despite treatment advances, diabetic eye disease remains a leading cause of vision loss worldwide. Diabetic macular edema (DME) is a common cause of vision loss in diabetic patients. The pathophysiology is complex and involves multiple pathways that ultimately lead to central retinal thickening and, if untreated, visual loss. First-line treatment of DME has evolved from focal/grid laser established by the Early Treatment of Diabetic Retinopathy Study (ETDRS) to intravitreous pharmacologic therapy. Landmark prospective clinical trials examining the effect of intravitreous injections of vascular endothelial growth factor (VEGF) inhibitors in the treatment of DME have demonstrated improved visual outcomes over focal grid laser. This review focuses on the scientific evidence treatment of DME, disease pathophysiology, clinical disease course, current treatment standards, and emerging novel therapeutic approaches.